The autophagic regulation of rosiglitazone-promoted adipocyte browning - Li, Yue; Zheng, Wanqing; Li, Xinhang; Lue, Zhengwei; Liu, Yun; Wu, Jiaying; Zhang, Xiangnan (Frontiers in Pharmacology, 2024)
Browning of white adipocytes is considered an efficient approach to combat obesity. Rosiglitazone induces thermogenetic program of white adipocytes, remaining the underlying mechanisms elusive. Here we reported that rosiglitazone promoted adipocytes browning and inhibited autophagy. Rapamycin, an autophagy inducer, reversed adipocytes browning induced by rosiglitazone. The autophagy inhibition by rosiglitazone did not prevent mitochondria clearance, which was considered to promote adipose whitening. Instead, autophagy inhibition increased p62 nuclear translocation and stabilized PPARγ-RXRα heterodimer, an essential transcription factor for adipocytes browning. We found that rosiglitazone activated NRF2 in mature adipocytes. Inhibition of NRF2 by ML385 reversed the autophagy inhibition and pro-browning effect of rosiglitazone. Taken together, our study linked autophagy inhibition with rosiglitazone-promoted browning of adipocytes and provided a mechanistical insight into the pharmacological effects of rosiglitazone.